2012
DOI: 10.1111/fwb.12020
|View full text |Cite
|
Sign up to set email alerts
|

Influence of food‐web structure on the biodegradability of lake sediment

Abstract: Summary 1. Sediment plays a key role in internal nutrient cycling and eutrophication in lakes. However, studies focusing on the efficiency of the biomanipulation techniques for improving the control of primary producers have rarely examined the effects of changes in food‐web structure on the sediment biochemical composition and biodegradability. 2. In a 1‐year experiment conducted in large replicated mesocosms, we tested how the absence or presence of a zooplanktivorous fish (roach, Rutilus rutilus) affected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…; Harrault et al . ) therefore affecting the productivity in the brown food web. In terrestrial ecosystems, productive plants have strong effects on microflora through their control on litter quality (Wardle et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…; Harrault et al . ) therefore affecting the productivity in the brown food web. In terrestrial ecosystems, productive plants have strong effects on microflora through their control on litter quality (Wardle et al .…”
Section: Discussionmentioning
confidence: 99%
“…Experiments have also shown that brown food webs respond strongly to the quality and quantity of dead organic matter, which is controlled by the structure of the green food web in both aquatic (Harrault et al . ; Danger et al . ) and terrestrial ecosystems (Bardgett & Wardle ; Wardle et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas the bottom-up effects of inorganic nutrients or light on aquatic ecosystems are well known (see Urabe et al, 2002;Cebrian & Lartigue, 2004;Hessen et al, 2004;Dickman, Vanni & Horgan, 2006;Spivak et al, 2007), those of SOM have more rarely been studied. Moreover, as the sediment biodegradability seems to be linked to its OM composition (Allard et al, 2011;Danger et al, 2012;Harrault et al, 2012), an interesting issue is whether different sediment compositions could lead to different bottom-up forcing on aquatic food webs. As DOM can originate from sediment biodegradation, sediment could be responsible for a bottom-up control for the whole food web, through the availability of resources for basal organisms (phytoplankton and bacterioplankton).…”
Section: Introductionmentioning
confidence: 99%
“…According to the results of Spivak et al (2007), Allard et al (2011 and Harrault et al (2012), we hypothesised that: Three treatments were compared: enclosures without added sediment (S 0 ), enclosures with carbon-poor sediment (S 1 ) and enclosures with carbonrich sediment (S 2 ).…”
Section: Introductionmentioning
confidence: 99%